If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -1n = 0 Solving m + -1n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add 'n' to each side of the equation. m + -1n + n = 0 + n Combine like terms: -1n + n = 0 m + 0 = 0 + n m = 0 + n Remove the zero: m = n Simplifying m = n
| 10x+5=40x+20 | | 400X^2-1000=0 | | m+n=0 | | -8-15w=-13w | | 2d+e=8 | | x+5=10+4x | | -10+5d=10+9d | | x^2+4kx=5k^2 | | q-22=19 | | (2x-3)(x+1)-(x+1)(4x+2)=0 | | 3w+1=77 | | (2x+5)*7=4x+57 | | a=18x^2 | | 4x+5=-7x+8 | | 47x(103+19)= | | -1-3b=-10-6b | | 180-2x=4 | | X^2+49=1024 | | u+12=31 | | 2x+5*7=4x+57 | | 7+5x=-13 | | 4x-2x=180 | | 5x^2+12=5x | | 3(y+6)=13 | | 6+4x=-58 | | (a+b)+2a=180 | | 1+8+x=23 | | 8.3=4k-2.4 | | x^4-4x^3+4x^2-16x=0 | | Y=8x+4.9 | | -6(3x+8)=-18x-48 | | x^4-4x^3+4x^2=16x |